Effect of epistasis and environment on flowering time in barley reveals a novel flowering-delaying QTL allele - Afsharyan, Nazanin P (J Exp Bot, 2020)
Flowering time is a complex trait and has a key role in crop yield and adaptation to environmental stressors such as heat and drought. This study aimed to better understand the interconnected dynamics of epistasis and environment and look for novel regulators. We investigated 534 spring barley MAGIC DH lines for flowering time at various environments. Analysis of quantitative trait loci (QTLs), epistatic interactions, QTL × environment (Q×E) interactions, and epistasis × environment (E×E) interactions were performed with single SNP and haplotype approaches. In total, 18 QTLs and 2420 epistatic interactions were detected, including intervals harboring major genes such as Ppd-H1, Vrn-H1, Vrn-H3, and denso/sdw1. Epistatic interactions found in field and semi-controlled conditions were distinctive. Q×E and E×E interactions revealed that temperature influenced flowering time by triggering different interactions between known and newly detected regulators. A novel flowering-delaying QTL allele was identified on chromosome 1H (named ‘HvHeading’) and was shown to be engaged in epistatic and environment interactions. Results suggest that investigating epistasis, environment, and their interactions, rather than only single QTLs, is an effective approach for detecting novel regulators. We assume that barley can adapt flowering time to the environment via alternative routes within the pathway.